The housing careers of Indigenous urban households - Birdsall-Jones, Christina; Corunna, V. (Australian Housing and Urban Research Institute, 2008)
This research involved an ethnographic study of the housing careers of extended kin groups of Indigenous Australians in Perth, Carnarvon and Broome. It found that the strongest forces shaping the housing careers of urban Indigenous Australians are long term poverty, family and neighbourhood violence and social housing accessibility and management practices. The study found that the crisis in affordability and vacancy rates created considerable anxiety for those studied, and often resulted in overcrowding where individuals and families were forced to choose between homelessness and living with kinfolk. For many the ideal housing career was considered to be securing a Homeswest (public rental) home, in preference to all other rental options because it provides security of tenure for the household. Housing aspirations were shaped by family history however, and where a history of home ownership existed, younger generations were more likely to aspire to home ownership.